Principles of insecticide resistance management - Georghiou, G.P. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
The need for effective strategies in resistance management is becoming more pressing as the number of insecticide-resistant species continues to increase worldwide while insecticide resources are diminishing. Prospects for development of such strategies are enhanced by recent advances in knowledge on the biochemistry, molecular genetics, ecology, dynamics, monitoring, and other important aspects of resistance. The generally recognized approaches to resistance management are grouped under three principal categories: first, low selection pressure, supplemented by a strong component of non-chemical measures (management by moderation); second, elimination of the selective advantage of resistant individuals by increasing insecticide uptake through the use of attractants, or by suppressing of detoxication enzymes through the use of synergists (management by saturation); and third, application of multi-directional selection by means of mixtures or rotations of unrelated insecticides or by use of chemicals with multi-site action (management by multiple attack). These approaches are not mutually exclusive and elements from each can be used to formulate a season-long management program. The strategy chosen must be based on a thorough knowledge of the resistance implications of the candidate insecticides and of the biology and ecology of the species concerned, and must make use of all available non-chemical control measures.